2013
DOI: 10.1111/cen.12141
|View full text |Cite
|
Sign up to set email alerts
|

The effect of B cell depletion therapy on anti‐TSH receptor antibodies and clinical outcome in glucocorticoid‐refractory Graves' orbitopathy

Abstract: This case series adds to the growing literature demonstrating that RTX, administered in our patients with concomitant methylprednisolone, is safe and clinically effective in the treatment of active, moderate to severe and sight-threatening GO. Randomized controlled trials are now needed to confirm the efficacy of RTX for GO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 25 publications
(34 reference statements)
2
67
2
5
Order By: Relevance
“…This study suggests that the natural history of AAD is modifiable and that Addison's disease is potentially remediable by disease-modifying drugs targeted at the immune response. This is in line with Type 1 diabetes mellitus and Graves' ophthalmopathy, in which immunomodulatory drugs administered early on in natural history have also shown some success (105,106,107). The low but detectable serum cortisol at diagnosis demonstrates the persistence of adrenal steroidogenesis in some patients, which has the potential to be rescued by either immunomodulatory or regenerative approaches.…”
Section: Regenerative Medicine In Autoimmune Addison's Diseasesupporting
confidence: 61%
“…This study suggests that the natural history of AAD is modifiable and that Addison's disease is potentially remediable by disease-modifying drugs targeted at the immune response. This is in line with Type 1 diabetes mellitus and Graves' ophthalmopathy, in which immunomodulatory drugs administered early on in natural history have also shown some success (105,106,107). The low but detectable serum cortisol at diagnosis demonstrates the persistence of adrenal steroidogenesis in some patients, which has the potential to be rescued by either immunomodulatory or regenerative approaches.…”
Section: Regenerative Medicine In Autoimmune Addison's Diseasesupporting
confidence: 61%
“…Whether this might have led to a diminished benefit in the US patients is not yet known. A similar use of steroids was usually the case for the pretrial case series that reported benefit with the use of RTX (10,15,31), and there are no clinical data to indicate that a longer washout from steroids would in any way potentiate RTX response. The protocol employed in the 2 RCTs is outlined in Table 3.…”
Section: Analysis Of the Randomized Trials Characteristicsmentioning
confidence: 90%
“…The potential use of RTX in GO has previously been reported in the literature (17,(26)(27)(28)(29). However, the difference and importance of the present study is that the GO of this patient was the most severe of the published cases.…”
Section: Discussionmentioning
confidence: 50%